MIO-PLIOCENE CRUSTACEANS FROM THE CANARY ISLANDS, SPAIN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
There are few previous references to fossil crustaceans for the Neogene marine layers of the Canary Islands (Spain). The Mio-Pliocene marine sedimentary layers in the eastern islands (Gran Canaria, Fuerteventura and Lanzarote) were previously characterised by the presence of numerous fossil fauna, mainly anthozoans and molluscs, which correspond to an equatorial-typepalaeoclimate, warmer than the present climate. This Mio-Pliocene transition dated between 9.3 and 4.1 Ma. In this paper, 12 fossil crustacean taxa are identified and classified, including decapods and barnacles: Balanus concavus Bronn, 1831, Balanus spongicola Brown, 1827, Balanus perforatus Bruguière, 1789, Chenolobia testudinaria Linnè, 1767, Tetraclita cf. rubescens Darwin, 1854, Callianassa matsoni Rathbun, 1935, Callianassa sp., Upogebia sp, Eriphia aff. verrucosa (Forskal, 1775) , Maja sp., Scylla michelini Milne-Edwards, 1861 and Ocypode sp. Some of these taxa mean new references for the Atlantic islands and the North African Atlantic and definitely enlarge the palaeographic distribution of Neogene crustaceans beyond the Mediterranean region, extending it to the North Atlantic. Particularly significant are the presence of Tetraclita cf. rubescens ,this being the first reported fossil occurrence of this barnacle outside the North America Pacific coasts, and Chenolobia testudinaria , indicating for the first time the existence of marine turtles in these islands during the Neogene. These results are coherent with previous research hypothesising the existence of a flow of surface water between the Pacific and Atlantic in the Mio-Pliocene transition (Central American Seaway, CAS) which explains the arrival of organisms, in larval stage, from Central America to the Canary Islands.